2007
DOI: 10.1103/physrevd.75.074011
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic corrections toJ/ψexclusive and inclusive double charm production atBfactories

Abstract: In order to clarify the puzzling problems in double charm production, relativistic corrections at order v 2 to the processes e + e − → J/ψ + η c and e + e − → J/ψ + cc at B factories are studied in non-relativistic quantum chromodynamics. The short-distance parts of production cross sections are calculated perturbatively, while the long-distance matrix elements are estimated from J/ψ and η c decays up to errors of order v 4 . Our results show that the relativistic correction to the exclusive process e + e − → … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
195
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(220 citation statements)
references
References 38 publications
21
195
4
Order By: Relevance
“…This K factor is roughly consistent with what is obtained through actual higher-order NRQCD calculations [28,30]. Although we extract this constant through the Υ(4S) → J/ψ + η c process, we will assume it is universal in all other double charmonium decay channels of Υ(nS).…”
Section: Phenomenology a Determination Of K From B Factories Mesupporting
confidence: 63%
See 2 more Smart Citations
“…This K factor is roughly consistent with what is obtained through actual higher-order NRQCD calculations [28,30]. Although we extract this constant through the Υ(4S) → J/ψ + η c process, we will assume it is universal in all other double charmonium decay channels of Υ(nS).…”
Section: Phenomenology a Determination Of K From B Factories Mesupporting
confidence: 63%
“…This process is closely related to the contiuum J/ψ + η c production in e + e − annihilation, which has recently aroused much attention since the measurements were first released by Belle collaboration [11]. Rather unexpectedly, it is shortly found that the leading-order NRQCD prediction to the production cross section falls short of the data by about one order of magnitude [21,22], which subsequently triggered intensive theoretical efforts to resolve this alarming discrepancy [23,24,25,26,27,28,29,30].…”
Section: Single-photon Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the attempts in [23,24] open a way to connect the predictions of hard quarkonium exclusive productions within the collinear factorization directly to those made within the NRQCD factorization (for examples, the many theoretical calculations based on NRQCD factorizations [25][26][27][28][29][30][31][32][33][34][35][36][37][38], triggered by the recent experimental measurements of charmonium exclusive productions at B-factories [39][40][41]). In particular, in [42,43], the authors have shown that the collinear factorization indeed can reproduce the exact asymptotic behavior of NRQCD predictions at the leading logarithms (LL) and next-toleading order (NLO) of the strong coupling α s , respectively, for a certain class of the quarkonium exclusive productions, if one employs the leading twist LCDAs calculated in [24]; and the ERBL equations can be used to resum the large logarithms appearing the NRQCD factorization calculations for the exclusive quarkonium productions, while such resummation cannot be done within the NRQCD factorization.…”
Section: Jhep06(2014)121mentioning
confidence: 99%
“…As an important example, the Belle and the LHCb collaborations [13,14] have measured the J/ψ production associated with a cc pair, which however show large discrepancies from the NRQCD predictions [15][16][17][18][19][20][21][22]. For instance, the predicted angular distribution of J/ψ is different from * Electronic address: zhansun@cqu.edu.cn † Electronic address: wuxg@cqu.edu.cn ‡ Electronic address: hfzhang@ihep.ac.cn the Belle data, and the predicted J/ψ production crosssection is lower than the LHCb data by about one order of magnitude.…”
Section: Introductionmentioning
confidence: 99%